2019
DOI: 10.1111/bjd.17851
|View full text |Cite
|
Sign up to set email alerts
|

Atrophic acne scar: a process from altered metabolism of elastic fibres and collagen fibres based on transforming growth factor‐β1 signalling

Abstract: Summary Background Atrophic acne scar, a persistent sequela from acne, is undesirably troubling to many patients due to its cosmetic and psychosocial aspects. Although there have been some reports emphasizing the role of early inflammatory responses in atrophic acne scarring, evolving perspectives on the detailed pathogenic processes are promptly needed. Objectives Examining the histological, immunological and molecular changes in early acne lesions susceptible to atrophic scarring can provide new insights to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 43 publications
3
51
1
3
Order By: Relevance
“…14,15 Furthermore, our previous clinical studies found that the injection of BTA in the early postoperative can decrease the scar formation and reduce the scar width in median sternotomy wound. Many studies have demonstrated that BTA not only reduces the wound tension to decrease scar formation, but also prevents the excessive deposition of collagen, 16,17 which was confirmed in the present study. These previous studies indicate that BTA is involved in the scar fibrosis process.…”
Section: Discussionsupporting
confidence: 87%
“…14,15 Furthermore, our previous clinical studies found that the injection of BTA in the early postoperative can decrease the scar formation and reduce the scar width in median sternotomy wound. Many studies have demonstrated that BTA not only reduces the wound tension to decrease scar formation, but also prevents the excessive deposition of collagen, 16,17 which was confirmed in the present study. These previous studies indicate that BTA is involved in the scar fibrosis process.…”
Section: Discussionsupporting
confidence: 87%
“…Transforming growth factor-β (TGFβ), IL-6, MMP, IGF-1, and B cells are found in keloid/hypertrophic scar tissues [ 37 , 38 ]. In atrophic scars, TLR4, IL-2, IL-10, tissue inhibitor of metalloprotease 2 (TIMP2), JUN, and TGFβ are elevated [ 39 , 40 ]. Immunological responses are different between patients with and without scarring [ 15 ].…”
Section: Pathophysiological Targets For Acne Treatmentmentioning
confidence: 99%
“…It arises from disorganised production and deposition of collagen in the dermis resulting in visibly depressed scars. The major types of atrophic scars are boxcar, ice pick, and rolling scars 25,32,33 . To date, with various patterns and profiles, there is no uniform treatment for acne scar 3,31,34 .…”
Section: Discussionmentioning
confidence: 99%